Unraveling the difference in flavor characteristics of Huangjiu fermented with different rice varieties using dynamic sensory evaluation and comprehensive two-dimensional gas chromatography–quadrupole mass spectrometry - Yu, Haiyan; Li, Qiaowei; Guo, Wei; Ai, Lianzhong; Chen, Chen; Tian, Huaixiang (Frontiers in Nutrition, 2023)
To investigate the specific differences in flavor characteristics of Huangjiu fermented with different rice varieties, dynamic sensory evaluation, comprehensive two-dimensional gas chromatography-quadrupole mass spectrometry (GC × GC–qMS) and multivariate statistical analysis were employed. Dynamic sensory evaluation methods including temporal dominance of sensations (TDS) and temporal check all that apply (TCATA) were applied to explore the differences and variations in sensory attributes. The sensory results showed that the intensity of astringency and post-bitterness in the Huangjiu fermented with glutinous rice was weaker while ester and alcoholic aroma were more prominent than the one fermented with japonica rice. The results of free amino acids and aroma compounds analysis indicated that the amino acids were mainly sweet and bitter amino acids, and some key aroma compounds were predominant in the Huangjiu fermented with glutinous rice, such as ethyl butyrate (OAV: 38–59), 3–methylthiopropionaldehyde (OAV: 47–96), ethyl caprylate (OAV: 30–38), while nonanal, phenyl acetaldehyde and vanillin contributed significantly to the Huangjiu fermented with japonica rice. The multivariate statistical analysis further confirmed that 17 compounds (VIP > 1 and p < 0.05) could be supposed to be the key compouns that cause significant flavor differences in Huangjiu samples fermented with different brewing rice. Moreover, partial least-squares analysis revealed that most compounds (ethyl butyrate, 3-penten-2-one, isoamyl acetate, and so on) correlated with ester and alcoholic aroma. The results could provide basic data and theoretical basis for the selection of raw materials in Huangjiu.